Pengaruh Edukasi Kesehatan Terhadap Peningkatan Pengetahuan Dan Perilaku Hidup Bersih Dan Sehat (PHBS) - Widiastuti (Nursing Practice Journal, 2025)
Clean and Healthy Living Behavior (PHBS) is an important effort in preventing disease in the community. Routine education provided by health workers is expected to increase knowledge and change community behavior for the better. This study aims to determine the effect of health education on improving community knowledge and behavior of clean and healthy living (PHBS). The study design used a pre-post test with a single group. A sample of 100 respondents was selected using purposive sampling. The research instrument was a PHBS knowledge and behavior questionnaire. Data analysis used a paired t-test and a Wilcoxon. The results showed a significant difference in knowledge and behavior before and after education (p < 0.001). From the results of observations, it was seen that the community was able to change several negative behaviors, especially regarding environmental cleanliness. Thus, it can be concluded that providing health education influences the level of community knowledge and behavior related to PHBS